A Chest‐Conformable, Wireless Electro‐Mechanical E‐Tattoo for Measuring Multiple Cardiac Time Intervals - Sarnab Bhattacharya; Mohammad Nikbakht; Alec Alden; Philip Tan; Jieting Wang; Taha A. Alhalimi; Sangjun Kim; Pulin Wang; Hirofumi Tanaka; Animesh Tandon; Edward F. Coyle; Omer T. Inan; et al. (Advanced Electronic Materials, 2023)
Abstract Cardiovascular diseases are the leading cause of death globally. Noninvasive, accurate, and continuous cardiovascular monitoring can enable the preemptive detection of heart diseases and timely intervention to prevent serious cardiac complications. However, unobtrusive, ambulatory, and comprehensive cardiac monitoring is still a challenge as conventional electronics are rigid, heavy, or consume too much power for long‐term measurement. This work presents a thin (200 µm), stretchable (20%), lightweight (2.5 g), wireless, and low‐power (<3 mW) cardiac monitoring device that conforms to the human chest like a temporary tattoo sticker, correspondingly known as an e‐tattoo. This chest e‐tattoo features dual‐mode electro‐mechanical sensing—bio‐electric cardiac signals via electrocardiography and mechanical cardiac rhythm via seismocardiography. A unique peripheral synchronization strategy between the two sensors enables the measurement of systolic time intervals like the pre‐ejection period and the left ventricular ejection time with high accuracy (error = −0.44 ± 8.74 ms) while consuming very low power. The e‐tattoo is validated against clinically approved gold‐standard instruments on five human subjects. The good wearability and low power consumption of this e‐tattoo permit 24‐h continuous ambulatory monitoring.